PENGARUH CITRA MEREK, KELAYAKAN HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA OLIVE FRIED CHICKEN YOGYAKARTA (Studi Kasus Pada Konsumen Olive Fried Chicken di Kota Yogyakarta) - Ester Lian; Yesi Eliana Br Ginting (Jurnal Manajemen, 2022)
This study aims to test the brand image, price feasibility, and product quality against the purchasing decision at Olive Fried Chicken Yogyakarta. The population in this study is Olive Fried Chicken Yogyakarta customers who have several branches in Yogyakarta and who have made purchases at Olive Fried Chicken Yogyakarta. The data source used is primary data, this sampling technique method uses a questionnaire method using a total sample of 110 respondents. The analysis method of this study used multiple linear regression analysis using the spss tool version 25. The classical assumption test used has met the specified criteria; t-tests and regressions showed variables of brand image, price feasibility, and product quality had a significant positive effect on purchasing decisions. Olive Fried Chicken Yogyakarta company is expected to pay attention to product quality strategies, price feasibility, and maintain a good brand image because it can influence purchasing decisions made by consumers. Olive Fried Chicken Yogyakarta company is expected to further maintain and improve the brand image and product quality by increasing discounts or discounts to improve purchasing decisions.